HUBUNGAN PENGETAHUAN PERAWAT TENTANG HEALTH ASSOCIATED INFECTIONS (HAIs) DENGAN PENERAPAN PRINSIP STERIL PEMASANGAN INFUS DI RUMAH SAKIT UMUM DAERAH H. SAHUDIN KUTACANE - Julwansa Saragih; Riska Wani Eka Putri Perangin-Angin (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Health Associated Infections (HAIs) are infections that occur in hospitals. One of the infections that occurs is bloodstream infections. This infection often occurs in patients who are infusions to prevent infection, nurses must use aseptic-aseptic techniques. Nurses' knowledge about HAIs is one of the things that can influence a person to apply sterile principles in order to prevent infection. The purpose of this study was to determine the relationship between nurses' knowledge about Health Associated Infections (HAIs) and the application of the sterile principle of infusion at the H. Sahudin Kutacane Regional General Hospital, Southeast Aceh Regency. The type of research used is descriptive correlation with cross sectional design. The sample of this research is the implementing nurse at the Regional General Hospital H. Sahudin Kutacane, Southeast Aceh Regency as many as 33 nurses. The sampling technique is accidental sampling. The results of the study obtained that the majority of nurses' knowledge was sufficient, the application of the sterile principle was good. Chi-square statistical test obtained p value = 0.016, this shows that there is a relationship between nurses' knowledge about Health Associated Infections (HAIs) with the application of sterile principles of infusion at the H. Sahudin Kutacane Regional General Hospital, Southeast Aceh Regency. Suggestions for nurses to pay more attention to septic-aseptic techniques when performing infusions.